A kind of nano hollow carbon sphere and its preparation method and application
The chemical vapor deposition method uses solid solution templates to deposit carbon atoms into nano-hollow carbon spheres, and the catalyst is removed by acid treatment, which solves the problem of difficult template removal in traditional template methods and improves yield and purity.
Patent Information
- Application Number
- CN202411574705.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the preparation of nano hollow carbon spheres by traditional template method, the template is difficult to remove, resulting in lower yield.
By chemical vapor deposition, a solid solution prepared in situ by the catalyst precursor as a template was used to deposit carbon atoms to form nano-hollow carbon spheres, and the catalyst was removed by acid treatment.
The yield and purity of nano-hollow carbon spheres are improved, the use of additional templates is avoided, and the purification process is simplified.
Smart Images

Figure CN119160879B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalysts, and in particular to a nano hollow carbon sphere and a preparation method and application thereof. Background Art
[0002] Hollow carbon nanospheres (HCS) are hollow spherical structures formed by curling up multi-layer graphene. They are considered to be particularly attractive functional materials due to their good uniformity, high thermal stability, high packing density and good conductivity, and have attracted the interest of many researchers. HCS can be prepared by template method, but the traditional template method for synthesizing HCS has problems such as difficulty in removing the template (such as silica) and low yield. Summary of the invention
[0003] The main purpose of the present application is to provide a nano hollow carbon sphere and a preparation method and application thereof, aiming to solve the technical problem that the template is difficult to remove in the traditional template method.
[0004] To achieve the above-mentioned purpose, the present application provides a method for preparing nano hollow carbon spheres, comprising: adding MgO to an aqueous solution of a metal salt to obtain a catalyst precursor; forming a solid solution of the catalyst precursor through a heating process of a chemical vapor deposition method, and depositing carbon atoms obtained by decomposing a carbon source on the solid solution to obtain crude nano hollow carbon spheres; and purifying the crude nano hollow carbon spheres to obtain nano hollow carbon spheres.
[0005] Optionally, adding MgO to the aqueous solution of the metal salt for reaction includes: preparing the aqueous solution of the metal salt; adding MgO to the aqueous solution of the metal salt, and sequentially stirring, drying, grinding, and calcining.
[0006] Optionally, the metal salt includes Fe(NO3)3·9H2O and Mn(NO3)2, the molar ratio of iron element to manganese element in the metal salt is (1-4):1, and the loading amount of MgO is 3-10 wt%.
[0007] Optionally, stirring, drying, grinding and calcining are performed in sequence, including: stirring at a temperature of 25-30°C for 25-35 minutes, heating to 80-100°C and stirring until viscous; drying at a temperature of 70-100°C for 12-20 hours; grinding, and calcining at a temperature of 450-600°C for 2-4 hours.
[0008] Optionally, the carbon source includes a combination of one or more of anhydrous ethanol, methane, ethylene, and acetylene; the catalyst precursor is formed into a solid solution through a heating process of a chemical vapor deposition method, and the carbon atoms obtained by decomposing the carbon source are deposited on the solid solution, including: placing the catalyst precursor in a reactor with an inert atmosphere, and the catalyst precursor is formed into a solid solution through a heating process of a chemical vapor deposition method; the carbon source is introduced into the reactor, and the carbon atoms obtained by decomposing the carbon source are deposited on the solid solution.
[0009] Optionally, a catalyst precursor is placed in a reactor with an inert atmosphere, and the catalyst precursor forms a solid solution through a heating process of a chemical vapor deposition method; a carbon source is introduced into the reactor, and carbon atoms obtained by decomposing the carbon source are deposited on the solid solution, including: placing a catalyst precursor in a reactor, introducing hydrogen into the reactor and heating it to a reduction temperature; replacing hydrogen with an inert gas, and heating it to a growth temperature, so that the catalyst precursor forms a solid solution; the carbon source is purged into the reactor by argon gas for a growth reaction, so that the carbon source is decomposed into carbon atoms, and the carbon atoms are deposited on the solid solution.
[0010] Optionally, the heating rate is 5-10°C / min, the reduction temperature is 600°C-800°C, the growth temperature is 900-1000°C, and the growth reaction time is 20-40min.
[0011] Optionally, the crude nano hollow carbon spheres are purified, including: purifying the crude nano hollow carbon spheres with dilute acid.
[0012] In addition, to achieve the above purpose, the present application also provides a nano hollow carbon sphere, which is obtained by the above preparation method.
[0013] In addition, to achieve the above purpose, the present application also provides an application of nano hollow carbon spheres, and the above nano hollow carbon spheres are used for catalytic hydrogenation reactions.
[0014] The present invention provides a nano hollow carbon sphere and a preparation method and application thereof. The invention firstly decomposes Fe(NO3)3·9H2O and Mn(NO3)2 into Fe2O3 and MnO2 by an impregnation method, and loads the Fe2O3-MnO2 / MgO on a MgO carrier to form Fe2O3-MnO2 / MgO, and then reduces the Fe2O3-MnO2 / MgO in a hydrogen atmosphere, and obtains a solid solution (Mg2O3-MnO2 / MgO) at a growth temperature. 0.9 Mn 0.1 O and Mg 0.91 Fe 0.09O), namely Fe-Mn / MgO, the solid solution is used as a template for HCS growth, and carbon atoms obtained by high-temperature decomposition of a carbon source are deposited on the solid solution through chemical vapor deposition to obtain crude HCS, and no external template is required in the process; in the purification stage, the catalyst can be removed only by acid treatment, thereby improving the purity of HCS; the prepared HCS has rich functional groups, large porosity and rich pore structure, and can be used to prepare efficient hydrogenation catalysts for nitrogen heterocyclic compounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of a process for preparing a nano hollow carbon sphere according to an embodiment of the present application;
[0016] Figure 2 This is the X-ray diffraction pattern of the crude HCS obtained in Example 1 of the method for preparing nano hollow carbon spheres of the present application;
[0017] Figure 3 This is the X-ray diffraction pattern of HCS obtained in Example 1 of the method for preparing nano hollow carbon spheres of the present application;
[0018] Figure 4 This is a Raman spectrum of HCS obtained in Example 1 of a method for preparing nano hollow carbon spheres of the present application;
[0019] Figure 5 This is a low-magnification scanning electron microscope image of HCS obtained in Example 1 of a method for preparing nano hollow carbon spheres of the present application;
[0020] Figure 6 This is a transmission electron microscope image of HCS obtained in Example 1 of a method for preparing nano hollow carbon spheres of the present application;
[0021] Figure 7 The nitrogen adsorption-desorption isotherm of HCS obtained in Example 1 of the method for preparing nano hollow carbon spheres of the present application;
[0022] Figure 8 This is a pore size distribution diagram of HCS obtained in Example 1 of a method for preparing nano hollow carbon spheres of the present application;
[0023] Fig. 9 This is a Fourier infrared spectrum of HCS obtained in Example 1 of a method for preparing nano hollow carbon spheres of the present application;
[0024] Fig.10 This is a low-magnification scanning electron microscope image of HCS obtained in Comparative Example 1;
[0025] Fig.11 This is a low-magnification scanning electron microscope image of HCS obtained in Comparative Example 2;
[0026] Fig.12 This is an X-ray diffraction diagram of the catalyst obtained in the first embodiment in the application of a nano hollow carbon sphere in another embodiment of the present application;
[0027] Fig.13 This is a gas chromatogram of an object subjected to hydrogenation catalysis using the catalyst obtained in the first embodiment in an application of a nano hollow carbon sphere in another embodiment of the present application;
[0028] Fig.14 This is a gas chromatogram of another object subjected to hydrogenation catalysis using the catalyst obtained in the first embodiment in an application of a nano hollow carbon sphere in another embodiment of the present application.
[0029] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0030] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0031] The main solutions of the embodiments of this application are:
[0032] Since the prior art uses the traditional template method to prepare HCS, the template is difficult to remove, resulting in a low HCS yield. The present application provides a solution, which uses the solid solution prepared in situ by the catalyst precursor as a template during the heating process of the chemical vapor deposition method to increase the yield of nano hollow carbon spheres. The solid solution template is easy to remove, and no additional template needs to be added, which is convenient for purification.
[0033] Reference Figure 1 The first embodiment of the present application provides a method for preparing nano hollow carbon spheres, the method comprising:
[0034] Step S10, adding MgO to the aqueous solution of the metal salt to obtain a catalyst precursor.
[0035] The metal salt may include Fe(NO3)3·9H2O and Mn(NO3)2, and the molar ratio of iron to manganese in the metal salt may be (1-4):1. In this embodiment, if too much iron is added, more carbon nanotubes will grow, and too little iron will result in a lower HCS yield. The method for preparing the catalyst precursor may be an impregnation method, and the impregnation process includes sufficient mixing, drying and calcining.
[0036] In an exemplary embodiment, step S10 may specifically include:
[0037] Step S11, preparing an aqueous solution of a metal salt;
[0038] The metal salt may be added to water to completely dissolve the metal salt to form an aqueous solution of the metal salt.
[0039] Step S12, adding MgO to the aqueous solution of the metal salt, and stirring, drying, grinding and calcining are performed in sequence.
[0040] The loading of MgO is 3-10wt%, that is, the total content of iron and manganese loaded on MgO is 3-10% of the mass of MgO.
[0041] After adding MgO, it can be stirred at a temperature of 25-30°C for 25-35 minutes, then heated to 80-100°C and stirred until viscous, then dried at a temperature of 70-90°C for 12-20 hours, then ground, and calcined at a temperature of 450-600°C for 2-4 hours to obtain a catalyst precursor, namely Fe2O3-MnO2 / MgO.
[0042] Step S20, forming a solid solution of the catalyst precursor through a temperature increase process of a chemical vapor deposition method, and depositing carbon atoms obtained by decomposing the carbon source on the solid solution to obtain crude nano hollow carbon spheres.
[0043] In an exemplary embodiment, the carbon source may include a combination of one or more of anhydrous ethanol, methane, ethylene, and acetylene.
[0044] In an exemplary embodiment, step S20 may specifically include:
[0045] Step S21, placing the catalyst precursor in a reactor with an inert atmosphere, forming a solid solution of the catalyst precursor through a heating process of a chemical vapor deposition method; introducing a carbon source into the reactor, and allowing the carbon atoms obtained by decomposing the carbon source to be deposited on the solid solution to obtain crude nano hollow carbon spheres.
[0046] In a specific embodiment, step S21 may specifically be:
[0047] Step S211, placing a catalyst precursor in a reactor, introducing hydrogen into the reactor and heating it to a reduction temperature.
[0048] The heating rate is 5-10°C / min, and the reduction temperature is 600°C-800°C. In this embodiment, the reactor may be a high-temperature tube furnace. Further, step S211 may include evenly laying the catalyst precursor in a porcelain boat, then placing the porcelain boat in the tube furnace, and introducing hydrogen with a flow rate of 200sccm into the tube furnace to raise the temperature to the reduction temperature.
[0049] Step S212, replacing hydrogen with an inert gas, and raising the temperature to the growth temperature to allow the catalyst precursor to form a solid solution.
[0050] Among them, during the heating process, the catalyst precursor forms a solid solution Mg0.9 Mn 0.1 O and Mg 0.91 Fe 0.09 O.
[0051] Step S213, the carbon source is purged into the reactor by argon gas to perform a growth reaction, so that the carbon source is decomposed into carbon atoms, and the carbon atoms undergo a growth reaction in the solid solution to obtain crude nano hollow carbon spheres.
[0052] The inert gas may be argon gas, the flow rate of the argon gas is 60-500 sccm, the growth temperature is 900-1000°C, and the growth reaction time is 20-40 minutes. During the process, at the growth temperature, the carbon source decomposes into carbon atoms and is deposited on the solid solution.
[0053] Step S30, purifying the crude nano hollow carbon spheres to obtain nano hollow carbon spheres.
[0054] Exemplarily, the crude nano hollow carbon spheres can be purified by dilute acid to obtain nano hollow carbon spheres; wherein the dilute acid can be dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid, the mass fraction of the acid used is 1-10wt%, and the stirring speed is 150-350r / min.
[0055] In this embodiment, the aqueous solution of Fe(NO3)3·9H2O and Mn(NO3)2 is firstly mixed with MgO by the impregnation method, firstly stirred at room temperature, then stirred by heating to obtain a viscous mixture, then dried and ground, and finally calcined to decompose Fe(NO3)3·9H2O and Mn(NO3)2 into Fe2O3 and MnO2 to obtain Fe2O3-MnO2 / MgO, i.e., catalyst precursor. Then, the catalyst precursor is reduced in a hydrogen atmosphere, and a solid solution (MgO) is formed during the heating process. 0.9 Mn 0.1 O and Mg 0.91 Fe 0.09O), at the same time, the carbon source decomposes at high temperature (growth temperature) to obtain carbon atoms, and through chemical vapor deposition, the solid solution is used as a template for the growth of HCS (nano hollow carbon spheres), and carbon atoms are deposited on the template to obtain crude nano hollow carbon spheres. No external template is required in the above process; during the heating process of chemical vapor deposition, the solid solution prepared in situ by the catalyst precursor is used as a template to increase the yield of nano hollow carbon spheres. In the purification stage, the catalyst can be removed only by acid treatment, and the purity of HCS is improved; the prepared HCS has a large porosity and rich pore structure. In addition, it was found through experiments that if only Fe(NO3)3·9H2O is used as the raw material, the MgO carrier only loads Fe2O3. At this time, Fe2O3 is reduced to Fe with higher activity, and no solid solution is formed. Fe is the growth site of carbon nanotubes. If only Mn(NO3)2 is used as the raw material, the MgO carrier only loads MnO2, and the Mg formed by the chemical vapor deposition process 0.9 Mn 0.1 O solid solution size is small, carbon is coated on the surface, and the HCS size is small after purification with dilute acid. Therefore, when the metal salt in this embodiment includes Fe(NO3)3·9H2O and Mn(NO3)2, Mg 0.91 Fe 0.09 O particles are larger in size and carbon is coated on the surface, so the HCS formed is larger in size and has a larger surface porosity, which is beneficial as a carrier for catalytic hydrogenation.
[0056] In some exemplary embodiments, the specific process of the purification treatment is: adding the crude nano hollow carbon spheres obtained in step S20 to a hydrochloric acid solution, stirring, filtering and washing at room temperature until the sample reaches neutrality, and then drying at a temperature of 50-70°C for 11-14h to obtain purified HCS.
[0057] In this embodiment, hydrochloric acid solution and Mg 0.9 Mn 0.1 O、Mg 0.91 Fe 0.09 O reacts to convert into salt and water, and then is filtered and washed to remove the solid solution. The amount of hydrochloric acid solution added is not limited as long as the effect of removing the solid solution can be achieved. For example, 100 ml of a hydrochloric acid solution with a concentration of 1 mol / L can be added to remove the solid solution.
[0058] Example 1
[0059] Step S110, according to the molar ratio of iron element to manganese element being 4:1, Fe(NO3)3·9H2O and Mn(NO3)2 are added into water to completely dissolve them, thereby obtaining an aqueous solution of metal salts;
[0060] Step S120, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 30 minutes, heating to 80°C and stirring until viscous, drying at 70°C overnight, grinding, and calcining at 450°C for 3 hours to obtain a catalyst precursor, wherein the MgO loading is 3wt%;
[0061] Step S130, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, hydrogen gas with a flow rate of 200 sccm is introduced into the tube furnace, and the temperature is increased to 600° C. at a heating rate of 10° C. / min;
[0062] Step S140, replacing hydrogen with argon, raising the temperature to 900°C, blowing ethanol vapor into a tube furnace with an argon flow rate of 500 sccm for a 30-minute growth reaction, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain crude HCS;
[0063] Step S150, adding 300 mg of HCS crude sample to 50 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain HCS.
[0064] The HCS crude sample obtained in step 140 of this embodiment was tested, and the test results were: Figure 2 The XRD patterns of Fe-Mn / MgO and Mn / MgO catalysts prepared in this example show that the peak of MgO is slightly shifted, with a series of diffraction peaks at 2θ of 36.8°, 42.8°, 62.1°, 74.4°, and 78.3°, which can be attributed to the Mg formed during the CVD process. 0.91 Fe 0.09 O solid solution (111), (200), (220), (311), (222) crystal planes [PDF#77-2365]; in addition, the diffraction peaks at 2θ of 36.7°, 42.6°, and 61.9° can be attributed to the Mg generated during the CVD process. 0.9 Mn 0.1 O solid solution (111), (200), (220) crystal planes (PDF#36-1377). It can be seen that a solid solution was formed during the preparation process of this example, and the solid solution served as a template for the growth of HCS.
[0065] The HCS material obtained in step 150 of this embodiment was subjected to component testing, and the test results were as follows: Figure 3This is the XRD pattern of the HCS material prepared in this example. Only the diffraction peak at 2θ of 24.6° is observed, which is attributed to the 110 crystal plane of carbon [PDF#89-8493]. This shows that dilute hydrochloric acid can remove the solid solution and obtain high-purity HCS.
[0066] The HCS material obtained in step 150 of this embodiment was subjected to a performance test, and the test results were as follows: Figure 4 This is the Raman graph of the HCS material prepared in this example. In the graph, at 1280cm -1 The disordered carbon atom vibration mode is called D peak, 1540cm -1 The phonon vibration mode of sp2-bonded carbon atoms in the graphite plane is called the G peak. From the Raman spectrum, it can be seen that the IG / ID value is not high, which shows that the defect degree of HCS is relatively large. Figure 5 This is a SEM image of the HCS material prepared in this example. It can be seen from the image that the sample is spherical, hollow inside, and has a large number of pore structures. Figure 6 This is a TEM image of the HCS material prepared in this example. It can be seen from the figure that the HCS presents a transparent disc-like structure with a hollow structure, and the HCS has openings at the edge of the disc, indicating that the synthesized material is indeed HCS. Figure 7 and Figure 8 The nitrogen adsorption-desorption isotherm and pore size distribution diagram of the HCS material prepared in this example; it can be seen from the isotherm diagram that the HCS material has the characteristics of type IV adsorption-desorption isotherm and exhibits an H4 type hysteresis loop, indicating that HCS has a large number of pore structures; it can be seen from the pore size distribution diagram that the pore size distribution is mainly concentrated in 5-100nm, and the specific surface area of HCS is 266.7m 2 / g.
[0067] Fig. 9 This is the Fourier infrared spectrum of the HCS material prepared in this example. -1 The spectral bands nearby are considered to be the peaks of C=C vibration, 3200~3430 cm -1 The nearby absorption band belongs to the peak generated by the OH stretching vibration of interlayer or free H2O; 1394cm -1 The nearby peak belongs to the bending vibration of the hydroxyl group -COH in the HCS structure, 1085 cm -1 The nearby peaks belong to the stretching vibration of C-OH on HCS; the above oxygen-containing functional groups can provide anchoring points for the loading of metal ions, which is beneficial for impregnation loading and improving the loading rate when used in the preparation of hydrogenation catalysts.
[0068] Example 2
[0069] Step S110, according to the molar ratio of iron element to manganese element of 3:1, Fe(NO3)3·9H2O and Mn(NO3)2 are added into water to completely dissolve them, so as to obtain an aqueous solution of metal salts;
[0070] Step S120, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 25 minutes, then heating to 85°C and stirring until viscous, then drying at 80°C overnight, then grinding, and calcining at 550°C for 2 hours to obtain a catalyst precursor; wherein the loading amount of MgO is 6 wt%;
[0071] Step S130, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, hydrogen gas with a flow rate of 200 sccm is introduced into the tube furnace, and the temperature is increased to 700° C. at a heating rate of 10° C. / min;
[0072] Step S140, replacing hydrogen with argon, raising the temperature to 950°C, and blowing ethanol vapor into a tube furnace with argon at a flow rate of 60 sccm to carry out a growth reaction for 20 minutes. After the reaction is completed, stop introducing ethanol and cool to room temperature in an argon atmosphere to obtain crude HCS;
[0073] Step S150, adding 300 mg of HCS crude sample to 100 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain HCS.
[0074] Example 3
[0075] Step S110, according to the molar ratio of iron element to manganese element being 1:1, Fe(NO3)3·9H2O and Mn(NO3)2 are added into water to completely dissolve them, thereby obtaining an aqueous solution of metal salts;
[0076] Step S120, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 35 minutes, then heating to 100°C and stirring until viscous, then drying at 90°C overnight, then grinding, and calcining at 600°C for 2 hours to obtain a catalyst precursor, wherein the MgO loading is 10wt%;
[0077] Step S130, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, 200 sccm of hydrogen is introduced into the tube furnace, and the temperature is increased to 800° C. at a heating rate of 10° C. / min;
[0078] Step S140, replacing hydrogen with argon, raising the temperature to 1000°C, blowing ethanol vapor into a tube furnace with an argon flow rate of 200 sccm for a 40-minute growth reaction, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain crude HCS;
[0079] Step S150, adding 300 mg of HCS crude sample to 95 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain HCS.
[0080] Example 4
[0081] Step S110, according to the molar ratio of iron element to manganese element of 2:1, Fe(NO3)3·9H2O and Mn(NO3)2 are added into water to completely dissolve them, so as to obtain an aqueous solution of metal salts;
[0082] Step S120, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 30 minutes, heating to 90°C and stirring until viscous, drying at 80°C overnight, grinding, and calcining at 520°C for 2.5 hours to obtain a catalyst precursor; wherein the loading amount of MgO is 7wt%;
[0083] Step S130, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, hydrogen gas with a flow rate of 200 sccm is introduced into the tube furnace, and the temperature is increased to 750° C. at a heating rate of 10° C. / min;
[0084] Step S140, replacing hydrogen with argon, raising the temperature to 1000°C, blowing ethanol vapor into a tube furnace with an argon flow rate of 300 sccm for a 25-minute growth reaction, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain crude HCS;
[0085] Step S150, adding 300 mg of HCS crude sample to 100 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain HCS.
[0086] Example 5
[0087] Step S110, according to the molar ratio of iron element to manganese element being 4:1, Fe(NO3)3·9H2O and Mn(NO3)2 are added into water to completely dissolve them, thereby obtaining an aqueous solution of metal salts;
[0088] Step S120, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 25 minutes, heating to 90°C and stirring until viscous, drying at 70°C overnight, grinding, and calcining at 580°C for 2 hours to obtain a catalyst precursor; wherein the loading amount of MgO is 9wt%;
[0089] Step S130, evenly spread 500 mg of the catalyst precursor in a porcelain boat, then put the porcelain boat into a tube furnace, introduce 200 sccm of hydrogen into the tube furnace, and heat the furnace to 720° C. at a heating rate of 10° C. / min;
[0090] Step S140, replacing hydrogen with argon, raising the temperature to 950°C, blowing ethanol vapor into a tube furnace with argon at a flow rate of 350 sccm to carry out a growth reaction for 40 minutes, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain crude HCS;
[0091] Step S150, adding 300 mg of HCS crude sample to 100 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 2.5 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain HCS.
[0092] Comparative Example 1
[0093] Step S210, adding Mn(NO3)2 into 50 mL of water to completely dissolve it, to obtain an aqueous solution of metal salt;
[0094] Step S220, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 30 minutes, then heating to 90°C and stirring until viscous, then drying at 70°C overnight, then grinding, and calcining at 450°C for 3 hours to obtain a catalyst precursor; wherein the total metal content of the MgO carrier is 1.8 wt%;
[0095] Step S230, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, hydrogen gas with a flow rate of 200 sccm is introduced into the tube furnace, and the temperature is increased to 600° C. at a heating rate of 10° C. / min;
[0096] Step S240, replacing hydrogen with argon, raising the temperature to 900°C, blowing ethanol vapor into a tube furnace with an argon flow rate of 500 sccm for a 30-min growth reaction, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain a crude HCS sample;
[0097] Step S250, adding 300 mg of HCS crude sample to 50 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60° C. oven and drying it for 12 h to obtain the HCS material.
[0098] Fig.10 This is a SEM image of the HCS material obtained in this comparative example. It can be seen from the image that the HCS material has a smaller particle size and less pore structure.
[0099] Comparative Example 2
[0100] Step S310, adding Fe(NO3)3·9H2O into 50 mL of water to completely dissolve it, to obtain an aqueous solution of metal salt;
[0101] Step S320, adding MgO to the aqueous solution of the metal salt, stirring at room temperature for 30 minutes, then heating to 90°C and stirring until viscous, then drying at 70°C overnight, then grinding, and calcining at 450°C for 3 hours to obtain a catalyst precursor; wherein the total metal content of the MgO carrier is 8.2 wt%;
[0102] Step S330, 500 mg of the catalyst precursor is evenly spread in a porcelain boat, and then the porcelain boat is placed in a tube furnace, hydrogen gas with a flow rate of 200 sccm is introduced into the tube furnace, and the temperature is increased to 600° C. at a heating rate of 10° C. / min;
[0103] Step S340, replacing hydrogen with argon, raising the temperature to 900°C, blowing ethanol vapor into a tube furnace with an argon flow rate of 500 sccm for a 30-minute growth reaction, stopping the introduction of ethanol after the reaction is completed and cooling to room temperature in an argon atmosphere to obtain a crude carbon material sample;
[0104] Step S350, adding 300 mg of HCS crude sample into 50 mL of 10 wt% hydrochloric acid solution, stirring at room temperature for 3 h to allow the HCS crude sample to fully react with the dilute hydrochloric acid solution to remove the catalyst; then filtering and washing the sample until the pH is 7, and then placing the washed and filtered black sample in a 60 ° C oven and drying it for 12 h to obtain a carbon material.
[0105] Fig.113 is a SEM picture of the carbon material obtained in this comparative example. It can be seen from the picture that the grown carbon material is carbon nanotubes.
[0106] On the basis of the above-mentioned embodiment, the second embodiment of the present application provides a nano hollow carbon sphere, which is prepared by the preparation method of the above-mentioned embodiment.
[0107] In this embodiment, the nano hollow carbon spheres have a large porosity and a rich pore structure and a high purity.
[0108] On the basis of the above-mentioned embodiments, the second embodiment of the present application provides an application of nano hollow carbon spheres, where the nano hollow carbon spheres are used for catalyst hydrogenation reaction.
[0109] In this embodiment, the nano hollow carbon spheres obtained in the above embodiment are used as carriers, and metals are loaded thereon to prepare hydrogenation catalysts, which can be used for catalysis of nitrogen heterocyclic compound hydrogenation reactions. For example, the nitrogen heterocyclic compound can be 2.5-dimethylpyrazine, N-methylindole hydrogenation reaction; the metal can be Pd or other metals. This embodiment is described by taking Pd as an example, and the metal Pd is loaded on the carrier, and the loading amount of Pd is 3-10wt% of the carrier.
[0110] Step S160, weigh 11.76 mg of palladium acetate and dissolve it in 50 mL of dichloromethane, add 50 mg of HCS obtained in the above example, stir at room temperature 25° C. until it becomes viscous, place in a vacuum oven at 60° C. and dry for 12 h to obtain a catalyst;
[0111] Step S170, evenly spread the catalyst in a porcelain boat, place the porcelain boat in the middle of a tubular furnace, and perform a reduction reaction in a hydrogen atmosphere at a heating rate of 2°C / min from room temperature to 300°C for 2 hours, then replace the hydrogen with argon and cool to room temperature to obtain a Pd / HCS catalyst.
[0112] The Pd / HCS catalyst is applied to the hydrogenation of 2,5-dimethylpyrazine, wherein the temperature of the 2,5-dimethylpyrazine hydrogenation reaction is 30-60°C and the reaction time is 6-12h;
[0113] 26.6 mg of Pd / HCS catalyst and 54 μL of 2,5-dimethylpyrazine were placed in a water-free and oxygen-free reaction tube, and 1 ml of hexafluoroisopropanol was added as a solvent. Hydrogen was introduced and stirred at 30°C for 12 h to obtain a reaction system.
[0114] The reaction system was centrifugally washed with ethanol and then vacuum rotary evaporated to obtain the product 2,5-dimethylpiperazine dissolved in ethanol and hexafluoroisopropanol. The gas chromatogram was then measured by gas chromatograph to calculate the conversion rate of the hydrogenation reaction of 2,5-dimethylpyrazine.
[0115] Fig.12 is the XRD pattern of Pd / HCS catalyst, in which the diffraction peaks at 2θ of 40.0°, 46.5°, and 68.1° are attributed to the (111), (200), and (220) crystal planes of Pd (PDF#88-2335). Fig.13 This is a gas chromatogram of 2,5-dimethylpyrazine. From the spectrum, it can be seen that there is a peak near 4.29. According to the measurement results of the standard curve, the peak at 3.9 belongs to the raw material 2.5-dimethylpyrazine, and the peak at 4.29 belongs to the characteristic peak of 2,5-dimethylpiperazine. In addition to the peaks of solvent ethanol and hexafluoroisopropanol and the product observed in the spectrum, the peak of the raw material 2,5-dimethylpyrazine is weak, indicating that the hydrogenation reaction of 2,5-dimethylpyrazine is relatively complete, and the Pd / HCS catalyst obtained by the above example has an excellent catalytic effect, and the conversion rate is greater than 99%.
[0116] Pd / HCS catalysts are used for the hydrogenation reaction of N-methylindole, wherein the temperature of the N-methylindole hydrogenation reaction is 80-120°C and the reaction time is 6-12h:
[0117] Take 26.6 mg of Pd / HCS catalyst and 66 μL of N-methylindole in an anhydrous and oxygen-free reaction tube and react at 120°C for 12 hours;
[0118] The above products were tested by gas chromatograph to obtain a gas chromatogram, such as Fig.14 From the spectrum, we can see that there is a peak at 5.5, but there are almost no peaks at 7.5 and 7.8. According to the calibration results, the peak at 5.5 belongs to octahydroindole, 7.5 belongs to tetrahydroindole, and 7.8 belongs to the raw material indole. It can be seen that there are almost no tetrahydroindole and indole peaks, and the octahydroindole peak is larger, indicating that the hydrogenation of indole is relatively complete, the catalyst works well, the conversion rate is greater than 99%, and the selectivity is greater than 99%.
[0119] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing nano hollow carbon spheres, characterized in that: include: Adding MgO to an aqueous solution of a metal salt to obtain a catalyst precursor, wherein the metal salt includes at least manganese; The catalyst precursor is formed into a solid solution by a temperature-raising process of chemical vapor deposition, and carbon atoms obtained by decomposing a carbon source are deposited on the solid solution to obtain a crude nano hollow carbon sphere, wherein the carbon source includes a combination of one or more of anhydrous ethanol, methane, ethylene, and acetylene; Purifying the crude nano hollow carbon spheres to obtain nano hollow carbon spheres; The step of forming a solid solution of the catalyst precursor by a temperature-raising process using a chemical vapor deposition method and depositing carbon atoms obtained by decomposing a carbon source on the solid solution comprises: The catalyst precursor is placed in a reactor with an inert atmosphere, and the catalyst precursor is formed into the solid solution through a temperature increase process of a chemical vapor deposition method; a carbon source is introduced into the reactor, and carbon atoms obtained by decomposing the carbon source are deposited on the solid solution; The catalyst precursor is placed in a reactor with an inert atmosphere, and the catalyst precursor is formed into a solid solution through a temperature increase process of a chemical vapor deposition method; a carbon source is introduced into the reactor, and carbon atoms obtained by decomposing the carbon source are deposited on the solid solution, comprising: Placing the catalyst precursor in a reactor, introducing hydrogen into the reactor and raising the temperature to a reduction temperature; Replacing the hydrogen with an inert gas and raising the temperature to a growth temperature so that the catalyst precursor forms a solid solution; The carbon source is purged into the reactor by argon gas to perform a growth reaction, so that the carbon source is decomposed into carbon atoms, and the carbon atoms are deposited on the solid solution.
2. The method for preparing nano hollow carbon spheres according to claim 1, characterized in that: The step of adding MgO to the aqueous solution of the metal salt for reaction comprises: preparing an aqueous solution of a metal salt; MgO is added to the aqueous solution of the metal salt, and stirring, drying, grinding and calcining are performed in sequence.
3. The method for preparing nano hollow carbon spheres according to claim 1, characterized in that: The metal salt includes Fe(NO3)3·9H2O and Mn(NO3)2, the molar ratio of iron element to manganese element in the metal salt is (1-4):1, and the loading amount of MgO is 3-10 wt%.
4. The method for preparing nano hollow carbon spheres according to claim 2, characterized in that: The stirring, drying, grinding and calcining are carried out in sequence, comprising: Stir at 25-30°C for 25-35 minutes, then heat to 80-100°C and stir until it becomes viscous; Dry at 70-100°C for 12-20h; Grind and calcine at 450-600℃ for 2-4h.
5. The method for preparing nano hollow carbon spheres according to claim 1, characterized in that: The heating rate is 5-10°C / min, the reduction temperature is 600°C-800°C, the growth temperature is 900-1000°C, and the growth reaction time is 20-40min.
6. The method for preparing nano hollow carbon spheres according to claim 1, characterized in that: The purification process of the crude nano hollow carbon spheres comprises: The crude nano hollow carbon spheres are purified by using dilute acid.
7. A nano hollow carbon sphere, characterized in that: The nano hollow carbon spheres are obtained by the preparation method according to any one of claims 1 to 6.
8. An application of nano hollow carbon spheres, characterized in that: The nano hollow carbon spheres described in claim 7 are used for catalytic hydrogenation reactions.
Citation Information
Patent Citations
Hollow carbon sphere supported metal particle catalyst as well as preparation method and application thereof
CN113649004A